Prevalence of Premenstrual Syndrome among Adolescent Girls in the Selected Schools in Kathmandu, Nepal - Manandhar, Pratima; Neupane, Leejana (Nepal Medical College Journal, 2022)
The global prevalence of premenstrual syndrome is 47.8%. This study was conducted to assess to assess prevalence of premenstrual syndrome among adolescent girl students among selected schools in Kathmandu. A descriptive cross sectional study was conducted among total 150 students. They were selected by using proportionate stratified random sampling technique. Data were collected using standard PMS scale (r =0.81) through self-administered method. Data were analyzed in SPSS version 16 using descriptive statistics and inferential statistics. The mean age and standard deviation was 14.43 years ± 1.143 years with range of 11-16 years among 150 respondents. Among them, majority of respondent (84.0%) had premenstrual syndrome. Assessment of severity of premenstrual syndrome found that the minority of respondents (0.6%) had mild, 54.7% had moderate, 24.0% had severe and 4.7% had very severe PMS. Premenstrual syndrome was significantly associated with family history of PMS (p=0.041), number of pads used per day during period (p=0.032), junk food consumption (p=0.007), physical exercise (p=0.020), experience of stress (p=0.006). Thus it can be concluded that, most of the adolescent girls have experienced PMS ranging from mild to very severe symptoms. Therefore, it would be good if school can organize regular screening program and adolescent girl’s friendly school environment to identify the problem on timely.